2020
DOI: 10.1155/2020/5850627
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Typical Professional Programs for Mechanical Analysis of Interlayer Bonding of Asphalt Pavement Structure

Abstract: The mechanical analysis of interlayer bonding problem of asphalt pavement is performed by the elastic layered system theory or finite element method (FEM); then, a lot of specialized programs based on the above theories emerged successively, of which BISAR3.0 and EverStressFE are quite representative. In order to further clarify the characteristics of BISAR3.0 and EverStressFE for investigating interlayer bonding problem of asphalt pavement, this paper will carry out a comprehensive comparison from the specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The mechanical response of asphalt pavement structure is greatly affected by different interlayer bonding conditions [7][8]. In this paper, the tensile strain at the bottom of asphalt layer under continuous and slip conditions is calculated to analyze the influence of interlayer contact conditions on mechanical response, and the results are shown in figure 10.…”
Section: Effect Of Interlayer Bonding Conditionmentioning
confidence: 99%
“…The mechanical response of asphalt pavement structure is greatly affected by different interlayer bonding conditions [7][8]. In this paper, the tensile strain at the bottom of asphalt layer under continuous and slip conditions is calculated to analyze the influence of interlayer contact conditions on mechanical response, and the results are shown in figure 10.…”
Section: Effect Of Interlayer Bonding Conditionmentioning
confidence: 99%
“…Pavement responses computation in the BISAR program generates complete calculation results in a pavement structure due to various loading categories and predictions of pavement structures. To further expand on the program's accuracy, a comparison of BISAR and EverStressFE was carried out to investigate the interlayer bounding problem of the asphalt pavement system [62]. The output of the results indicated that both programs' discrepancy in analyzing the mechanical response of the asphalt pavement interlayer problem does not provide any significant difference, and further concluded that the professional tools are excellently useful.…”
Section: Basirmentioning
confidence: 99%
“…These structures often face challenges related to interlayer bonding due to factors like construction techniques and environmental conditions. Insufficient bonding between the semi-rigid base and asphalt surface leads to an increased occurrence of reflective cracks in asphalt pavements, ultimately diminishing their service life [6][7][8]. Previous studies have shown that weakened interlayer bonding results in heightened tensile strain in the upper part of the interlayer, leading to a substantial reduction in the fatigue life of the asphalt pavement, up to 75.6% [9][10][11].…”
Section: Introductionmentioning
confidence: 99%